THE STRUCTURE AND COMPOSITION OF THE CONCEPT OF MIDDLE AGE - Khujamberdiyeva Gavhar Ilhom kizi (Innovate Conferences, 2025)
This article explores the linguistic and cultural representation of the concept of middle age in English and Uzbek languages. It analyzes how the term is defined, expressed, and perceived in both societies, focusing on lexical choices, metaphors, and cultural attitudes. While English often frames middle age as a period of transition or crisis, Uzbek language and culture tend to highlight it as a time of maturity, respect, and social responsibility. Through comparative analysis, the article reveals how language reflects deeper societal values regarding aging and life stages.
Keywords: middle age, linguocultural concept, age perception, Uzbek language, English language, conceptual metaphor, cultural values, midlife, maturity